2004
DOI: 10.1111/j.1365-2362.2004.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll‐like receptor 4 in the initiation and progression of atherosclerotic disease

Abstract: The family of Toll-like receptors ( TLRs) initiates an innate immune response after recognition of pathogen-associated molecular patterns (PAMPs). Evidence is accumulating that TLRs, and particularly TLR4, are important players in the initiation and progression of atherosclerotic disease. Not only exogenous ligands but also endogenous ligands that are expressed during arterial injury are recognized by TLR4. Mouse knockout studies and epidemiological studies of human TLR4 polymorphisms have demonstrated that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 77 publications
(111 reference statements)
1
102
0
4
Order By: Relevance
“…Although atherosclerosis is certainly a multigenic disease, two gene-targeted knockouts in mice, the LDL receptor and apolipoprotein E, provide excellent models for study (36), and direct in vivo evidence exists that TLR signaling plays a role in atherosclerosis (37,38). Two groups have demonstrated that MyD88, one of the TLR intracellular signaling molecules, participates in atherosclerosis.…”
Section: Studies In Gene-deficient Micementioning
confidence: 99%
“…Although atherosclerosis is certainly a multigenic disease, two gene-targeted knockouts in mice, the LDL receptor and apolipoprotein E, provide excellent models for study (36), and direct in vivo evidence exists that TLR signaling plays a role in atherosclerosis (37,38). Two groups have demonstrated that MyD88, one of the TLR intracellular signaling molecules, participates in atherosclerosis.…”
Section: Studies In Gene-deficient Micementioning
confidence: 99%
“…Our observation that Wnt5a is expressed in the macrophagerich regions of murine atherosclerotic tissue and the fact that TLR-4 has been implicated in atherosclerosis (4,17,31) led us to investigate the ability of murine macrophages to express Wnt5a RNA upon stimulation of the TLR-4 signal transduction cascade. RAW264.7 (murine macrophages) were treated with various concentrations of LPS, a ligand for TLR-4.…”
Section: Wnt5a Is Expressed In the Macrophage Region Of Murine Andmentioning
confidence: 99%
“…There is a growing body of evidence that suggests that aberrant TLR expression or signaling is involved in pathological inflammation (1,6,24). Specifically, TLR-4, a TLR that recognizes lipopolysaccharide (LPS), has been implicated in atherosclerosis (7,17,31).…”
mentioning
confidence: 99%
“…Incidence increased significantly over the last years, with Ͼ23,000 cases in the U.S. in 2002 (2). LD displays different clinical stages: erythema chronicum migrans (ECM) is associated with early localized infection; early disseminated infection commonly may include facial palsy as well as meningoencephalitis, the latter occurring more frequently in Europe as compared with the U.S. (3).…”
mentioning
confidence: 99%